Chapter Innovation and sustainability: the Italian scenario - Cataldo, Rosanna (Proceedings e report, 2021)
Society and policy makers demand innovation systems oriented towards several goals of sustainable development. Therefore, recent literature has dedicated a growing interest to both innovation and sustainability in the pursuit of environmental, economic and social development; in addition, the emerging topic of 'sustainable innovation' (and 'eco-innovation') seems to combine the main features of them. The definition of these concepts has been significantly changed during the last decades, and a broad discussion continues today about which indicators should be used to measure innovation, sustainability and their combination. The current paper investigates this relationship, and - in the authors' opinion - the research question connected to the impact of the innovative product (and service and process) solutions on sustainability can be addressed by means of a stable theoretical framework. To study the interaction between innovation and sustainability, the usage of specific territorial features might represent a useful perspective to manage short-and long-term environmental and economic issues. As for the theoretical model, the present article considers a specific technique suitable for investigating the entire set of characteristics involved in the model. From a public makers and managerial point of view, the possibility of improving the firm' efficiencies in terms of several dimensions of sustainable innovation represents a relevant topic that must be encouraged.